Differential Willingness to Pay for Kidney Transplantation From Living and Deceased Donors: Empirical Study Among End-Stage Kidney Disease (ESKD) Patients - Limor Dina Gonen PhD; Ya'arit Bokek-Cohen PhD; Pazit Azuri PhD; Mahdi Tarabeih PhD (SAGE Publishing, 2022)
Kidney transplantation has developed to the stage where it is currently the most cost-effective treatment for patients suffering from end-stage kidney disease (ESKD) and, when available, offers them the highest quality of life. Yet, kidney transplantation is challenged by cultural and traditional beliefs; thus, this study sought to evaluate the willingness to pay for a kidney transplant in a culturally sensitive population. A self-administered survey was completed by 734 end-stage kidney disease (ESKD) patients. A quantitative method and survey design were chosen and employed descriptive, correlational, nonparametric, and multivariate statistical tests. Participants were willing to pay a mean amount of $40 751.36 for a living donor kidney transplant, whereas the mean is considerably lower, $18 350.51, for a deceased donor kidney. Significant predictors of the willingness to pay (WTP) for a kidney transplant from a living donor and a deceased donor were found, among them: religiosity and ethnicity. The participants' willingness to pay for a kidney transplant could attest to significant benefits in enhancing patient well-being. The willingness to pay differentially for a donation from a deceased or a living donor stems from the higher chances of success with a living-donor organ as well as from moral and religious motives. In Israel kidney transplantation is not tradable in the free market and is fully funded by the state. The average cost of kidney transplantation in Israel is $61 714.50. Since the cost exceeds the utility and since the economic literature suggests that the funding of healthcare interventions should be provided up to the point where the costs of that funding equal the benefits that society derives from it, crucial revisions in public health policy should be made. Education may have a significant impact on the approach to kidney donation and organ donation in general.